Juvenile social experience generates differences in behavioral variation but not averages. (21st December 2018) - DiRienzo, Nicholas; Johnson, J Chadwick; Dornhaus, Anna
Abstract: Developmental plasticity is known to influence the mean behavioral phenotype of a population. Yet, studies on how developmental plasticity shapes patterns of variation within populations are comparatively rare and often focus on a subset of developmental cues (e.g., nutrition). One potentially important but understudied developmental experience is social experience, as it is explicitly hypothesized to increase variation among individuals as a way to promote "social niches." To test this, we exposed juvenile black widow spiders ( Latrodectus hesperus ) to the silk of conspecifics by transplanting them onto conspecific webs for 48 h once a week until adulthood. We also utilized an untouched control group as well as a disturbed group. This latter group was removed from their web at the same time points as the social treatment, but was immediately placed back on their own web. After repeatedly measuring adult behavior and web structure, we found that social rearing drove higher or significant levels of repeatability relative to the other treatments. Repeatability in the social treatment also decreased in some traits, paralleling the decreases observed in the disturbed treatments. Thus, repeated juvenile disturbance may decrease among-individual differences in adult spiders. Yet, social rearing appeared to override the effect of disturbance in some traits, suggesting a prioritization effect. The resulting individual differences were maintained over at least one-third of the adult lifespan and thus appear to represent stable, canalized developmental effects and not temporal state differences. These results provide proximate insight into how a broader range of developmental experiences shape trait variation. Abstract : Juvenile social experience increases adult behavioral differences, in some, but not all traits. This result indicates that juvenile experience may play an important role in shaping individual social niches. Unexpectedly, the disturbance from removing spiders from their containers generally reduced variation but increased how body size influenced behavior, suggesting that individuals have unique responses to different developmental experiences. These differences persisted for the duration of the experiment highlighting the long-term effects of developmental experience.